When threats become catalysts: cognitive job crafting, work meaningfulness, and employee proactivity in high-insecurity contexts - Liu, Lidan; Su, Yuhan; Wang, Zhongjun (Frontiers in Psychology, 2025)
Drawing on Conservation of Resources (COR) theory, this study examined how cognitive job crafting stimulated employee innovation behavior and organizational citizenship behavior (OCB) through work meaningfulness, and how job insecurity moderated these effects. Using a multi-source, employee-supervisor paired design, data were collected from 512 Chinese participants across diverse industries (e.g., manufacturing, technology, healthcare). Employees self-reported cognitive job crafting, work meaningfulness, and job insecurity, while supervisors evaluated innovation behavior and OCB. A moderated mediation analysis revealed that cognitive job crafting significantly enhanced work meaningfulness, which in turn promoted both innovation behavior and OCB. Job insecurity amplified these indirect effects: under high insecurity, the mediating role of work meaningfulness was stronger. These findings highlighted cognitive job crafting’s unique role as a low-resource strategy to counter uncertainty. By bridging COR theory with job crafting research, this study advanced a resource-based perspective on employee adaptability in unstable environments.